Persepsi Peternak Sapi Potong Terhadap Sistem Integrasi Sapi-Sawit Di Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi - Arya Gustian Jaya; Afriani Harahap; Eko Wiyanto (CV. SINAR HOWUHOWU, 2026)
This study aims to determine the perception level of beef cattle farmers toward the cattle-oil palm integration system and to analyze the factors influencing this perception in Kumpeh Ulu District, Muaro Jambi Regency. The method employed was a survey method, utilizing purposive sampling for both sample selection and village determination, with a total of 51 respondents. The data consisted of primary and secondary data, which were analyzed using descriptive analysis and multiple linear regression. The results indicated that the farmers' perception level toward the cattle-oil palm integration system fell into the